Morphoproteomic-Guided Host-Directed Therapy for Tuberculosis - Brown, Robert E.; Hunter, Robert L.; Hwang, Shen-An (Frontiers in Immunology, 2017)
In an effort to develop more effective therapy for tuberculosis (TB), research efforts are looking towards host directed therapy, reprogramming the body’s natural defenses to better control the infection. While significant progress is being made, the efforts are limited by lack of understanding of the pathology and pathogenesis of adult type TB disease. We have recently published evidence that the developing lesions in human lungs are focal endogenous lipid pneumonia that constitutes a region of local susceptibility in a person with strong systemic immunity. Since most such lesions regress spontaneously, the ability to study them directly with immunohistochemistry provides means to investigate why some progress to clinical disease while others asymptomatically regress. Furthermore, this should enable us to develop more effective host directed therapies. Morphoproteomics has proven to be an effective means of characterizing protein expression that can be used to identify metabolic pathways, which can lead to more effective therapies. The purpose of this perspective will argue that using morphoproteomics on human TB lung tissue is a particularly promising method to direct selection of host directed therapeutics.